2021
DOI: 10.3390/ijms22126392
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives of Natural Chlorophylls as Agents for Antimicrobial Photodynamic Therapy

Abstract: The rapid growth of drug-resistant bacteria all over the world has given rise to a major research challenge, namely a search for alternative treatments to which bacteria will be unable to develop resistance. Photodynamic therapy is an approach of this kind. It involves the use of photosensitizers in combination with visible light at a certain wavelength to excite the former and generate reactive oxygen species. Various synthetic heterocyclic compounds are used as photosensitizers. Of these, derivatives of natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 88 publications
0
39
0
Order By: Relevance
“…A clinical trial suggested oral curcumin together with visible light might be a new therapeutic method for moderate to severe plaque psoriasis [ 256 ]. Chlorophylls and derivatives as photosensitizers in PDT could be used to treat acne vulgaris and microbial infection [ 231 , 257 , 258 , 259 ]. In therapeutic PDT, the photosensitizers should absorb between 600 and 800 nm, and natural dyes might show potential as photosensitizers, which is worthy of further study.…”
Section: Resultsmentioning
confidence: 99%
“…A clinical trial suggested oral curcumin together with visible light might be a new therapeutic method for moderate to severe plaque psoriasis [ 256 ]. Chlorophylls and derivatives as photosensitizers in PDT could be used to treat acne vulgaris and microbial infection [ 231 , 257 , 258 , 259 ]. In therapeutic PDT, the photosensitizers should absorb between 600 and 800 nm, and natural dyes might show potential as photosensitizers, which is worthy of further study.…”
Section: Resultsmentioning
confidence: 99%
“…The ineffectiveness of PDT to Gram-negative bacteria is associated with the low permeability of their outer membrane for antibacterial agents. To improve the antimicrobial activity of photosensitizers, research groups are trying to synthesize their various derivatives, create conjugates, or use them in parallel with other compounds, e.g., antibiotics [13,43,44,[46][47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…The application of APDT as a complementary step of partial removal of dental caries appears as a favorable therapeutic candidate to stimulate dental practitioners in adopting minimal intervention procedures instead of old-fashioned restorative methods [22]. A photosensitizer penetrates a target cell without causing any adverse effects itself, which is very helpful [23].…”
Section: Application Of Natural Photosensitizers In Dental Cariesmentioning
confidence: 99%